Teachers’ demographic and occupational attributes predict feelings of hopelessness during the COVID-19 pandemic - Ghasemi, Farshad (Frontiers in Psychology, 2022)
The outbreak of the COVID-19 pandemic has resulted in many emotional consequences for teachers, including feelings of isolation, loneliness, and hopelessness. However, evidence on the prevalence of hopelessness and the associated factors in teachers during the pandemic is limited. The purpose of this research was to examine the prevalence of hopelessness in public school teachers and identify risk factors associated with it. A sample of 168 teachers aged 25 to 49 years participated in the study by completing the Socio-Demographic Questionnaire, the Beck Hopelessness Scale (BHS), and the Multi-Dimensional Scale of Perceived Social Support (MSPSS). The results revealed a moderate level of experienced hopelessness in teachers. Hopelessness prevalence was also significantly different across teacher gender (males = 79%), age groups (>40 = 77%), socioeconomic status (poor socioeconomic status = 70%), educational level (high school teachers = 79%), professional experience (experienced teachers = 82%), and perceived social support (low perceived social support = 79%). The results of a logistic regression analysis confirmed the effects of these demographic and occupational attributes on hopelessness by explaining approximately 71% of the variance in hopelessness feelings. Higher odds ratios were associated with age, socioeconomic status, and perceived social support, signifying the prominence of these factors in predicting hopelessness. The study contributes to identifying and screening teachers at risk of hopelessness in public schools and recommends promoting collegial/superior support as well as a positive school climate as the protective factors against hopelessness.